Wisdom in Israel and in the ancient near east: Presented to Professor Harold Henry Rowley by the Society for Old Testament study in association with the editorial board of Vetus Testamentum in celebration of his sixty-fifth birthday, 24 March 1955 - Noth, Martin; (1902-1968) (Netherlands, 1960)
The tribute paid to H. H. ROWLEY by Professor Martin Noth and Professor WINTON THOMAS will be felt by all British Old Testament scholars to express admirably their own sentiments. Nevertheless, it is entirely fitting that there should also be a further tribute in the English tongue from H. H. Rowley's own British colleagues who yield to none in their esteem for his person and their appreciation of his work.
Keywords: Rowley, H H -- (Harold Henry), -- 1890-1969 -- Bibliography